2012
DOI: 10.1161/atvbaha.112.255281
|View full text |Cite
|
Sign up to set email alerts
|

Platelets Derived From the Bone Marrow of Diabetic Animals Show Dysregulated Endoplasmic Reticulum Stress Proteins That Contribute to Increased Thrombosis

Abstract: Objective-Patients with diabetes mellitus have an increased risk of suffering atherothrombotic syndromes and are prone to clustering cardiovascular risk factors. However, despite their dysregulated glucose metabolism, intensive glycemic control has proven insufficient to reduce thrombotic complications. Therefore, we aimed to elucidate the determinants of thrombosis in a model of type 2 diabetes mellitus with cardiovascular risk factors clustering. Methods and Results-Intravital microscopy was used to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…The findings of the present study emphasize also the relevance of the multimeric structure and especially of the oxidation status of VWF multimers for their pro-thrombotic effects. This phenomenon, along with the documented intrinsic hyperactivity of platelets in type 2 diabetic patients [37], [38], can contribute to intensified adhesion, activation, and aggregation of platelets, favoring the occurrence of thrombotic complications in the arterial circulation. VWF has also other extra-haemostatic functions, including angiogenesis and leukocyte extravasation [39], [40], which can cooperate in inducing thrombotic events.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study emphasize also the relevance of the multimeric structure and especially of the oxidation status of VWF multimers for their pro-thrombotic effects. This phenomenon, along with the documented intrinsic hyperactivity of platelets in type 2 diabetic patients [37], [38], can contribute to intensified adhesion, activation, and aggregation of platelets, favoring the occurrence of thrombotic complications in the arterial circulation. VWF has also other extra-haemostatic functions, including angiogenesis and leukocyte extravasation [39], [40], which can cooperate in inducing thrombotic events.…”
Section: Discussionmentioning
confidence: 99%
“…They found that bone marrow cells derived from rats with hypercholesterolemia, obesity, and insulin resistance transferred an increased thrombotic risk to healthy recipients . The platelets derived from the bone marrow of diabetic fatty rats exhibited a dysregulated endoplasmic reticulum stress protein that promoted thrombosis in recipients . Using diabetic fatty rat models in the current study, the authors discovered that bone marrow cells from diabetic rat donors with cardiovascular risk factors induced proatherogenic alterations in the cholesterol profiles of otherwise healthy recipients by increasing low‐density lipoprotein (LDL), but not triglyceride, levels, whereas bone marrow cells derived from healthy donors did not .…”
mentioning
confidence: 81%
“…Bone marrow transplants were performed following a procedure previously proven to produce an effective engraftment of donor bone marrow in the recipients . Receptors were immunosuppressed with a combined therapy consistent of cyclophosphamide and busulfan prior to transplantation.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, cell therapy clinical trials using autologous bone marrow cells to improve myocardial function in heart failure or after infarction have failed to reproduce the promising results obtained in healthy mouse models and in studies performed with cells from healthy subjects . Moreover, we have described in a rat model that hypercholesterolemia and obesity with insulin resistance (with and without type 2 diabetes) induces alterations in bone marrow cells that transfer an increased thrombotic risk to transplanted healthy recipients . Therefore, the aim of this study was to analyze, in an animal model, whether transplantation of bone marrow cells from donors with clustering of CVRF affects cardiovascular risk in healthy recipients.…”
Section: Introductionmentioning
confidence: 99%